ANALISIS HUKUM TERHADAP PENYIMPANGAN PROGRAM BANTUAN SOSIAL BERKAITAN DENGAN UPAYA MENGATASI COVID-19 - Alde Karunia Syarvi; Zulfikar Jayakusuma; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research raises the background of the problem regarding LawNumber 20 of 2001 concerning Corruption Crimes Associated with LawNumber 2 of 2020 concerning State Financial Policy and Financial SystemStability for Handling the Corona Virus Disease 2019 (Covid-19)Pandemic. Second, Social Assistance Program Deviations Practices Seenfrom the Perspective of Law Number 20 of 2001 Related to Law Number 2of 2020. Third, regarding criminal responsibility for deviations fromsocial assistance programs related to efforts to tackle Covid-19.This study aims to: First, to know and understand the practice ofdeviating from social assistance from the perspective of Law Number 20of 2001 in relation to Law Number 2 of 2020. Second, To know and knowcriminal responsibility for deviations from social assistance programsrelated to Covid-19 countermeasures.This research uses juridical-normative research (library lawmethod) because the purpose of this research is to provide a systematicand comprehensive picture or picture. The data analysis used in thisresearch is qualitative, namely the descriptions made by the researcher onthe data collected by not using numbers but in the form of descriptions ofsentences arranged systematically according to the problems beingdiscussed.The results of this study can be drawn from the conclusion that thepractice of deviating social assistance from the perspective of LawNumber 20 of 2001 is associated with Law Number 2 of 2020 committedby an irresponsible party is an act of corruption because it has fulfilledthe elements - elements contained in Law Number 31 of 1999 jo. LawNumber 20 of 2001, this act is classified as a crime, namely corruption.Criminal liability for perpetrators of social assistance programirregularities related to efforts to deal with Covid-19 can be sentenced toimprisonment and fines or can also be sentenced to death, seeing thatcertain elements of circumstances are fulfilled during the Covid-19emergency.Keywords: Covid-19, Social Assistance, Corruption Crime